Cytokine Levels in Gestational Diabetes Mellitus: a Systematic Review of the Literature. (18th February 2013) - Gomes, Caio Perez; Torloni, Maria Regina; Gueuvoghlanian‐Silva, Bárbara Yasmin; Alexandre, Sandra Maria; Mattar, Rosiane; Daher, Silvia
Abstract : Problem: Gestational diabetes mellitus (GDM) is an inflammatory condition that involves unbalanced cytokine production. We carried out a systematic review on the relationship between GDM and maternal circulating levels of cytokines in the 2nd/3rd trimesters. Method of Study: Three electronic databases (MEDLINE, EMBASE and LILACS), were searched. Duplicate study selection, extraction and quality assessment was performed. Results: Twenty‐two studies with 1982 participants reporting levels of 9 cytokines (IL‐1B, IL‐2, IL‐6, IL‐10, IL‐13, IL‐18, IFN‐G, TGF‐B and TNF‐A) were included. Most studies differed considerably in selection criteria, sampling and assay methods and in reporting their results. Consequently, only two studies could be pooled: TNF‐A concentration was slightly higher in GDM than in control patients, although not significant (WMD = 0.45, 95% CI −0.34–1.23). Conclusions: New studies with well‐defined, more homogeneous methodological parameters are needed to detect whether there are significant differences in circulating levels of cytokines in patients with GDM.